(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Endraputra PN, Kuntaman K, Wasito EB, Shirakawa T, Raharjo D, Setyarini W. 2021. Profile variation of bla genes among non-lactose fermenting Gram negative bacilli between clinical and environmental isolates of Dr. Soetomo Hospital, Surabaya, Indonesia. Biodiversitas 22: 5047-5054. Carbapenem-resistant non-fermenter Gram-negative bacilli are notorious opportunistic pathogens in hospitalized patients and hospital environments. This study explored the carbapenemase gene among non-fermenter Gram-negative bacilli from hospital wastewater and clinical isolates in Dr. Soetomo Hospital, Surabaya, Indonesia. All samples were screened on MacConkey agar with meropenem 2 µg/ml and gene detected by Multiplex PCR. All samples were screened on MacConkey agar with meropenem 2 µg/ml and gene detected by Multiplex PCR. A total of 121 isolates consisted of 76 clinical (41 carbapenem-resistant Acinetobacter baumannii and 35 carbapenem-resistant Pseudomonas aeruginosa), 45 environmental isolates (6 carbapenem-resistant Pseudomonas aeruginosa and 32 carbapenem-resistant Pseudomonas spp.), and 7 screening samples (all CRPAs). Clinical isolates carbapenemase genes were identified, blaOXA-23-like 21 (28%), blaOXA-24-like 30 (39%), blaNDM-1 1 (1%), and blaIMP-1 6 (8%) while environmental isolates were blaOXA-23-like 5 (13%), blaOXA-24-like 4 (11%), blaOXA-48-like 2 (5%), blaNDM-1 13 (34%), blaVIM 12 (32%), and blaIMP-1 4 (11%). Rectal swab screening specimens presented blaOXA-23-like 3 (43%), blaOXA-24-like 3 (43%), and blaNDM-1 1 (14%). The carbapenemase gene pattern was different between clinical and environmental isolates. The blaOXA-23-like and blaOXA-24-like were most prevalent among in both clinical and wastewater, while blaVIM was mostly in wastewater. The presence of carbapenem-resistant non-fermenter Gram-negative bacilli carrying carbapenemase genes in hospital effluents indicated that the community river was seeded with an antimicrobial resistance gene.